1981
DOI: 10.1111/j.1095-8649.1981.tb03828.x
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of the gastric epithelium of the rainbow trout, Salmo gairdneri, Richardson

Abstract: Fine structural characteristics of the columnar mucus cells lining the surface and pits of the gastric mucosa, oxyntic cells lining the glands and the gastric endocrine cells were studied. The surface mucus cells, in addition to their primary involvement in production of mucus, showed structural adaptations. Release of the mucus vesicles was achieved by exocytosis. Transition from pit gland cells was abrupt since no mucus neck cells were observed. The oxyntic cells possessed apical and basal microvillous proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…This discrepancy could be related to different fixatives, technical procedures and antibodies used. As in bony fish (Ezeasor, 1981) and protochordates (Pestarino, 1983) all somatostatin-like cells are in contact with the lumen, even in the gastric portion, and generally have cytoplasmic processes which are relatively short in S. stellaris.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy could be related to different fixatives, technical procedures and antibodies used. As in bony fish (Ezeasor, 1981) and protochordates (Pestarino, 1983) all somatostatin-like cells are in contact with the lumen, even in the gastric portion, and generally have cytoplasmic processes which are relatively short in S. stellaris.…”
Section: Discussionmentioning
confidence: 98%
“…Observations at ultrastructural level showed that three types of cells (mucous, glandular and endocrine cells) were found in the stomach epithelium. According to Ezeasor (1981), mocus and glandular cells were involved in producing gastric juice. In other teleost fishes, the cells in the gastric glands are also called as oxyntopeptic cell, which are related to the synthesis of hydrochloric acid as well as pepsinogen.…”
Section: Discussionmentioning
confidence: 99%
“…The pinocytotic uptake and subsequent intracellular digestion of exogenous proteins by rectal epithelia has been documented frequently in both larval fish and adult stomachless fish (Noaillac-Depeyre & Gas, 1976;Watanabe, 1981Watanabe, , 1984Govoni et al, 1986;Caceci & Hrubec, 1990;Abaurrea et al, 1993). In stomachless species, protein digestion occurs intracellularly in the rectal epithelium (Govoni et al, 1986), as also in species with functional stomachs (Ezeasor, 1981;Morrison, 1987), probably increasing protein digestion efficiency, when gastric emptying is too frequent for complete hydrolysis of proteins in the stomach (Ezeasor, 1981). In a case such as this, the pinocytosis of proteins by the rectal cells would serve complementary to stomach function.…”
Section: Discussionmentioning
confidence: 99%